Towards a framework for identifying and engaging rural tourism route stakeholders in southern Africa - Mclaren, Linde; Heath, Ernie (Africanus: Journal of Development Studies, 2018)
Several southern African governments view rural tourism development as a strategy for employment creation in rural areas where few other opportunities for poverty alleviation exist. Rural tourism routes can attract tourists from developed tourism nodes to rural areas. On both the strategic and operational levels, rural tourism routes can only function effectively if they have the support and co-operation of the wide range of stakeholders in the route. While some stakeholders are readily identified, others are not immediately apparent or may not be recognised as stakeholders in the route. Based on a qualitative study, a framework is developed to identify and link the range of stakeholders in southern African rural tourism routes. Three different groups of stakeholders are identified; each play different roles in the sustainable success of a rural tourism route, namely demand-side stakeholders or visitors, core stakeholders or tourism service providers on the route, and enabling stakeholders, who influence both the route operations and the environment in which the route operates. Finally, recommendations are made for rural tourism route organisations to engage with a range of stakeholders through an inclusive membership structure of the route organisation. Further research is also suggested on the nature and format of route organisation and membership structures to ensure sustainable route development.